2016
DOI: 10.1038/srep27352
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a rhamnose utilization pathway and rhamnose-inducible promoters in Pichia pastoris

Abstract: The rhamnose utilization pathway in Pichia pastoris has not been clarified although this strain can grow well on rhamnose as a sole carbon source. In this study, four genes, PAS_chr4_0338, PAS_chr4_0339, PAS_chr4_0340, and PAS_chr4_0341, were, for the first time, predicted to be involved in rhamnose metabolism along with the previously identified gene PAS_chr1_4-0075. Moreover, expression of these genes, especially PAS_chr4_0341 and PAS_chr1_4-0075 designated as LRA4 and LRA3, was confirmed to significantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…However, to achieve specificity, we considered it unlikely that the originally described CGG-X 11 -CCG site [43], which is an exact replicate of the Gal4p responsive element, is the full recognition element. The extra T nucleotide we found was also present in the EMSA constructs used by Pardo and Orejas [43], in at least one half-site of the TCGG-X 11 -CGC motif found to be important for strong l -Rha-dependent induction of lra3 in Pichia pastoris [56], and in the shorter binding motif identified by Weirauch et al [46] (http://cisbp.ccbr.utoronto.ca/index.php). Therefore, we think it likely that the PDR-1/RhaR responsive element is represented by the TCGG-X 11 -CCGA motif.…”
Section: Discussionmentioning
confidence: 97%
“…However, to achieve specificity, we considered it unlikely that the originally described CGG-X 11 -CCG site [43], which is an exact replicate of the Gal4p responsive element, is the full recognition element. The extra T nucleotide we found was also present in the EMSA constructs used by Pardo and Orejas [43], in at least one half-site of the TCGG-X 11 -CGC motif found to be important for strong l -Rha-dependent induction of lra3 in Pichia pastoris [56], and in the shorter binding motif identified by Weirauch et al [46] (http://cisbp.ccbr.utoronto.ca/index.php). Therefore, we think it likely that the PDR-1/RhaR responsive element is represented by the TCGG-X 11 -CCGA motif.…”
Section: Discussionmentioning
confidence: 97%
“…A previous study preliminarily investigated several rhamnose-inducible promoters in Pichia pastoris . Among them, the transcription activities of two promoters, P LRA3 and P LRA4 , were higher than those of other promoters, including PAS_chr4_0338 promoter (P LRA1 ), PAS_chr4_0339 promoter (P LRA2 ), PAS_chr4_0340 promoter (P LRAR ) ( Liu et al, 2016 ), which indicated that LRA3 and LRA4 were rate-determining step enzymes related to rhamnose metabolism. Recombinant proteins under the control of the two promoters, especially P LRA3 , could be efficiently produced using rhamnose as the inducer ( Liu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cells were collected using centrifugation (12,000g) at 4 °C for 4 min and stored at − 80 °C before total RNA extraction. Total RNA extraction and trace DNA removal were performed according to previously described methods (Liu et al 2016). RNA concentration was determined with a Qubit ® 2.0 fluorometer (Life Technologies, CA, USA), and the quality was checked using an Agilent RNA 6000 Nano kit combined with an Agilent 2100 Bioanalyzer (Santa Clara, CA, USA).…”
Section: Production Determination Of Recombinant Proteinmentioning
confidence: 99%
“…Simultaneously, the promoters of LRA3 and LRA4, P LRA3 and P LRA4 , were identified as two strong rhamnoseinducible promoters (Jiao et al 2019;Liu et al 2016). Subsequently, a Pichia expression system based on P LRA3 , designated as the P LRA3 system, was developed using rhamnose as the inducer.…”
Section: Introductionmentioning
confidence: 99%